Recovering with Mental Healthy Generation Through Early Detection And Mental Health Education - Sulaihah, Sitti; Amir, Faisal; Suhron, M.; Hafidah, Lailatul; Fiddaroini, Fakhrun Nisa’ (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2024)
In order to emphasize the importance of mental health in line with World Mental Health Day 2023, this community service activity focuses on the initial launch of mental health awareness through screening and promotion of mental health as an initial movement for preventive and promotive efforts through strengthening mental health information within the scope of STIKES Ngudia Husada Madura. The service method is in the form of early detection by filling in the SRQ-20 instrument and mental health education. Participants in the October 10 2023 activity consisted of 230 female new students who lived in the dormitory and took part in mental health screening tools. The data obtained before the education was carried out was that the majority of students had no indication of mental health problems (normal) as many as 150 people (65,22%) and students who had indications of mental health problems (emotional mental disorders) were 80 people (34.78%). There was significant progress after mental health promotion, namely that 190 students (82,60%) had no indication of mental health problems (normal) and 40 students (17,40%) had indications of mental health problems (emotional mental disorders). Then it continued with mental health promotion on 11 October 2023 and ended with a mental health tool screening on 8 November 2023. The implementation of the activity went smoothly and received a good response from the target. Early detection of mental health is very important and needs to be socialized to students to prevent delays in treatment in the early phase.